Cryptocurrencies and anti-money laundering laws: the need for an integrated approach - Zul Kepli, Mohd Yazid; Zulhuda, Sonny (Emerald Publishing Limited, 2019)
This chapter attempts to clarify and describe the legal and regulatory framework for cryptocurrency with special focus on Malaysia and the threats that it poses from the anti-money laundering perspective. Currently, very few countries have legislations that regulate cryptocurrency. Nonetheless, the crazy surge in prices (to more than 20-folds at some point) has sent both legitimate investors and criminals flocking to cryptocurrencies. This chapter analyses and compares the official reports from various governments, writings of government officials, experts and scholars in journals and newspapers, interviews and draws conclusions on the legal framework of cryptocurrency, and money laundering challenges. The study notes that the decision of the US regulators in allowing Bitcoin futures to trade on major exchanges to be one of the reasons behind the sudden surge. The study also finds that the South Korean regulators’ approach in banning its financial institutions from dealing with virtual currency is a positive one. The chapter stresses that it is not adequate for regulators to warn the public to act with extreme caution and increase their understanding on the risks they take on if they choose to invest in cryptocurrencies. Instead, it is necessary to have comprehensive international and national laws and regulations for the control and management of cryptocurrencies. In addition, the anti-money laundering legal framework must be improved to cater to the new threats posed by cryptocurrency.